2021
DOI: 10.1101/2021.05.07.21256819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the depth and width of normal fetal Sylvian fissure by trans-cerebellar section

Abstract: Objective On the basis of retrospectively analysis the trans-cerebellar section showing the Sylvian fissure of normal fetus is better than trans-thalamic section in middle and late trimester, we prospectively established the normal reference range of developmental parameters related to the Sylvian fissure of normal fetus in the trans-cerebellar section in order to provide valuable information for the diagnosis of fetal cerebral cortical dysplasia. Methods A prospective cross-sectional study was conducted on 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…A prospective cross-sectional study conducted by Pingping et al [ 8 ] on 845 normal fetuses between 21 and 32 weeks of gestation studied the depth and width of the Sylvian fissure (SF) in relation to the gestational age and concluded that the depth of SF positively correlated with gestational weeks, whereas the width of SF was negatively correlated with gestational weeks, with correlation coefficients 0.751 and 0.825, respectively (all p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective cross-sectional study conducted by Pingping et al [ 8 ] on 845 normal fetuses between 21 and 32 weeks of gestation studied the depth and width of the Sylvian fissure (SF) in relation to the gestational age and concluded that the depth of SF positively correlated with gestational weeks, whereas the width of SF was negatively correlated with gestational weeks, with correlation coefficients 0.751 and 0.825, respectively (all p < 0.001).…”
Section: Introductionmentioning
confidence: 99%